Quain hernia - A rare cause of acute small bowel obstruction. A case report and an updated literature review. (December 2021) - MacDonald, Scott; Stokes, Emily; Macdonald, Angus; Sharaf, Usama
Abstract: Introduction and importance: Internal herniae are a rare cause of acute small bowel obstruction (SBO), accounting for <1% of all causes of SBO. Given their low incidence and often vague presenting symptoms there can be a delay in their diagnosis - which can lead to unnecessary morbidity for patients. Case presentation: We present a case of a 34 year-old nulliparous female who presented with acute abdominal pain and transpired to have a closed loop obstruction of her ileum through a congenital defect in her broad ligament, or a Quain hernia. Discussion: This paper will describe this case and provide an updated literature review of Quain herniae from recent research. With regards to surgical management of these hernia, both laparoscopic and open approaches are appropriate as long as appropriately trained surgical staff are involved. If a contraltateral defect in the Broad ligament is identified, this should be repaired prophylactically at the time in order to prevent future instances of internal herniation. Conclusion: Increased awareness of the potential presenting symptoms and radiological features of Quain hernia, as outlined in this paper, is vital in order to reduce patient morbidity and mortality. Highlights: Quain hernia is a subtype of internal hernia caused by a defect in the broad ligament. Their lack of recognition often leads to a delayed diagnosis and increased patient morbidity. Both open and laparoscopic repair are suitable in appropriately trained individuals. Contralateral defects should be fixed prophylactically to prevent future herniation.